Students’ Academic Flow During the Covid-19 Pandemic - Kristanti, Elisabeth; Atanus, Fidelis (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Academic flow is an important aspect that supports learning activities. COVID-19 pandemic has caused many problems, including in the field of education. Thus, the academic flow needs to be raised both by the students themselves and supported by their social environment, because flow conditions can be a medium for students to be able to learn optimally. Research with a quantitative approach aims to explore social support, time management, learning responsibility, and student academic flow and to determine the effect of social support, time management, and learning responsibility on students' academic flow. A sampling of 436 students through a simple random sampling technique. Collecting data using a questionnaire on a Likert scale. Data analysis using multiple regression tests. The results of the analysis show that there is an influence of social support, time management, and learning responsibility on students' academic flow. Thus, it can be concluded that there is a positive and significant effect of social support, time management, and learning responsibility on students' academic flow. For this reason, it is very important for students to be able to create their academic flow through high learning responsibilities, good time management, and social support from their environment, in order to learn optimally.